A case of apocrine hidrocystoma on the penis - Xiaohua TAO; Yuyu DENG; Meihua HE (Pifu-xingbing zhenliaoxue zazhi, 2022)
A case of apocrine hidrocystoma on the penis is reported. A 23-year-old man developed a skin-colored rice-sized papule on the penis shaft for 1 month. Histopathological examination showed normal epidermis and an enlarged empty cyst in the dermis. The cyst walls were composed of 1~2 layers of cells, with round or oval nucleus at the base of the cells. Apocrine secretion was evident. A diagnosis of apocrine hidrocystoma of the penis was made. The skin lesions were completely removed and followed up for 6 months without recurrence.